Respuesta :

fichoh

Answer:

∑j=15(5j−12)

Step-by-step explanation:

For j = 1 up to j = 5

j = 1

(5j - 12) = (5(1) - 12) = 5 - 12 = - 7

j = 2

(5j - 12) = (5(2) - 12) = 10 - 12 = - 2

j = 3

(5j - 12) = (5(3) - 12) = 15 - 12 = 3

j = 4

(5j - 12) = (5(4) - 12) = 20 - 12 = 8

j = 5

(5j - 12) = (5(5) - 12) = 25 - 12 = 13

(-7 + (-2) + 3 + 8 + 13)

Ver imagen fichoh

Answer:

(5j-12)

Step-by-step explanation:

Other person was right, took the test using the answer they gave.

Ver imagen foxchow400